Answer:
2
Explanation:
In order to solve a system using the additional method, we would need to multiply the first equation by '2' in order for the x’s to add out.
We have the following equations:
--- (1)
--- (2)
We will multiply equation (1) by 2 and equation (2) by 3 to cancel the x's.
![6x - 2 y = 6](https://img.qammunity.org/2020/formulas/mathematics/middle-school/fyurzjbycmj4hr3tn9ziv7vs4wj3vryamo.png)
![3 ( -2x + 2 y = 6 ) = -6x + 6y = 36](https://img.qammunity.org/2020/formulas/mathematics/middle-school/5gzenbz81h2miporycrg3zvl8sfsb97qr3.png)